2008
DOI: 10.1021/la703264x
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of “A−a” Knob−Hole Fibrin Interaction Revealed by Atomic Force Spectroscopy

Abstract: During blood vessel injury, fibrinogen is converted to fibrin, a polymer that serves as the structural scaffold of a blood clot. The primary function of fibrin is to withstand the large shear forces in blood and provide mechanical stability to the clot, protecting the wound. Understanding the biophysical forces involved in maintaining fibrin structure is of great interest to the biomedical community. Previous reports have identified the "A-a" knob-hole interaction as the dominant force responsible for fibrin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Recent studies by Averett et al provide direct evidence that the γ-nodules unfold in response to mechanical stress (33, 34). These authors developed a novel method to measure the forced dissociation of ‘A:a’ interaction using AFM.…”
Section: The γ–Nodulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies by Averett et al provide direct evidence that the γ-nodules unfold in response to mechanical stress (33, 34). These authors developed a novel method to measure the forced dissociation of ‘A:a’ interaction using AFM.…”
Section: The γ–Nodulesmentioning
confidence: 99%
“…In subsequent studies of multi-step ‘A:a’ bond rupture, Averett et al demonstrated that the force applied to hole ‘a’ through bound knob ‘A’ induced stepwise unfolding of the γ-nodule prior to rupture of the ‘A:a’ bond (33, 34). Remarkably, the strength of the ‘A:a’ bond was sufficient to survive through the unfolding events.…”
Section: The γ–Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a characteristic rupture pattern is observed in rupture of the molecular bond responsible for initial polymerization of fibrin. 21 For these interactions, it is suggested that the characteristic pattern consisting of two, four sequential ruptures originates from unfolding of a globular D domain of fibrin. A single-molecule nature of these ruptures is supported by the analysis of distributions of distances between rupture events and by the detailed kinetic analysis of distributions of rupture forces.…”
Section: Introductionmentioning
confidence: 99%
“…This fingerprint is often obtained from mechanical unfolding of "polyproteins", [17][18][19][20] or it naturally occurs during rupture of molecular bonds. 21,22 Stretching of a polyprotein with individual "monomers" corresponding to folded globular proteins shows the restoring force that exhibits a sawtooth-like rupture pattern. In this pattern, the peak force is interpreted as unfolding of individual domains, and the spacing between the peaks corresponds to the gain in length of unfolded regions.…”
Section: Introductionmentioning
confidence: 99%